Aplikasi Keselamatan Berbasis Smartphone dengan Integrasi Sinyal Sos Sebagai Solusi Pembentukan Masyarakat Tanggap Bencana - Ilma, Naviatul Ilma; Cendana Feoh, Agung Dewa; Saifudin, Wahyu Ahmat (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
Natural disasters are disasters caused by an event or a series of events caused by nature, it’s as varied as the form of earthquakes, tsunamis, volcanic eruptions, floods, droughts, hurricanes, and landslides (Law number 4 of 2007). Based on data cited from the Indonesian Central Statistics Agency (BPS) in 2018 the number of people who died due to natural disasters was 6,053 people. This data shows that community preparedness to face the threat of disaster optimally is needed. The idea of creating a smartphone-based safety application design equipped with SOS signal sending capabilities is planned to create a disaster response community and rescue response by related parties to reduce disaster risk with the use of the structured application. The synergy between various parties such as the community and also the government in the smooth running of information as quickly as possible will be the key to the effectiveness of this application. People in situations facing natural disasters can reach safe places with the help of an application that has been embedded in the feature to find out safe places for self-evacuation. If there is an emergency the user can also send an SOS signal to the server which will be picked up immediately by the patrol on duty.